A global lightning parameterization based on statistical relationships among environmental factors, aerosols, and convective clouds in the TRMM climatology. Issue 14 (21st July 2017) - Stolz, Douglas C.; Rutledge, Steven A.; Pierce, Jeffrey R.; van den Heever, Susan C.
Abstract: The objective of this study is to determine the relative contributions of normalized convective available potential energy (NCAPE), cloud condensation nuclei (CCN) concentrations, warm cloud depth (WCD), vertical wind shear (SHEAR), and environmental relative humidity (RH) to the variability of lightning and radar reflectivity within convective features (CFs) observed by the Tropical Rainfall Measuring Mission (TRMM) satellite. Our approach incorporates multidimensional binned representations of observations of CFs and modeled thermodynamics, kinematics, and CCN as inputs to develop approximations for total lightning density (TLD) and the average height of 30 dB Z radar reflectivity (AVGHT30). The results suggest that TLD and AVGHT30 increase with increasing NCAPE, increasing CCN, decreasing WCD, increasing SHEAR, and decreasing RH . Multiple‐linear approximations for lightning and radar quantities using the aforementioned predictors account for significant portions of the variance in the binned data set ( R 2 ≈ 0.69–0.81). The standardized weights attributed to CCN, NCAPE, and WCD are largest, the standardized weight of RH varies relative to other predictors, while the standardized weight for SHEAR is comparatively small. We investigate these statistical relationships for collections of CFs within various geographic areas and compare the aerosol (CCN) and thermodynamic (NCAPE and WCD) contributions to variations in the CF population in a partial sensitivity analysis based on multiple‐linear regression approximations computed herein. A global lightning parameterization is developed; the average difference between predicted and observed TLD decreases from +21.6 to +11.6% when using a hybrid approach to combine separate approximations over continents and oceans, thus highlighting the need for regionally targeted investigations in the future. Key Points: Multiple‐linear regression explains 69‐81% of average lightning and radar reflectivity behavior in the tropics and subtropics CCN, NCAPE, and WCD contribute significantly to variability in lightning density and radar reflectivity echo top height A global lightning parameterization incorporating aerosols and environmental thermodynamic factors is developed